Q. 1 B3.9( 23 Votes )

<span lang="EN-US

Answer :

Consider two binomials as x−2y and 2x−y

Now,to get the product of two binomials x−2y and 2x−y we use the


distributive law i.e. (x−2y)×( 2x−y) = x(2x)-x(y)-2y(2x)-2y(-y) = 2x2-xy-4xy + 4y2


Therefore ,the product of x−2y and 2x−y is 2x2 + 4y2-5xy.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics